Generation of Genetically Stable Human Direct-Conversion-Derived Neural Stem Cells Using Quantity Control of Proto-oncogene Expression - Kwon Daekee; Han Mi-Jung; Ji Minjun; Ahn Hee-Jin; Seo Kwang-Won; Kang Kyung-Sun (Elsevier, 2019)
As the human lifespan has increased due to developments in medical technology, the number of patients with neurological diseases has rapidly increased. Therefore, studies on effective treatments for neurological diseases are becoming increasingly important. To perform these studies, it is essential to obtain a large number of patient-derived neural cells. The purpose of the present study was to establish a technology that allows the high-efficiency generation of genetically stable, direct-conversion-derived neural stem cells (dcNSCs) through the expression of a new combination of reprogramming factors, including a proto-oncogene. Specifically, human c-MYC proto-oncogene and the human SOX2 gene were overexpressed in a precisely controlled manner in various human somatic cells. As a result, the direct conversion into multipotent dcNSCs occurred only when the cells were treated with an MOI of 1 of hc-MYC proto-oncogene and hSOX2 retrovirus. When MOIs of 5 or 10 were utilized, distinct results were obtained. In addition, the pluripotency was bypassed during this process. Notably, as the MOI used to treat the cells increased, expression of the p53 tumor suppressor gene, which is typically a reprogramming hurdle, increased proportionately. Interestingly, p53 was genetically stable in dcNSCs generated through direct conversion into a low p53 expression state. In the present study, generation of genetically stable dcNSCs using direct conversion was optimized by precisely controlling the overexpression of a proto-oncogene. This method could be utilized in future studies, such as in vitro drug screening using generated dcNSCs. In addition, this method could be effectively utilized in studies on direct conversion into other types of target cells. Keywords: c-Myc, direct conversion, direct-conversion-derived neural stem cells, MOI, p53